1965
DOI: 10.1002/macp.1965.020830118
|View full text |Cite
|
Sign up to set email alerts
|

The polymerization of vinyl acetate in aqueous solution initiated by potassium persulphate at 60°C.

Abstract: Polyvinyl acetate precipitates from aqueous solution as it is formed. When potassium persulphate is used as initiator the polymer suspension is stable and constitutes the principal locus of reaction. The effect of reaction conditions on the rate of polymerization and on the number of particles formed ha5 been studied. The surface charge density appears to be the factor which determines the number of particles formed and which limits the rate of reaction.ZUSAMMENFASSUNG:Polyvinylacetat f a t bei seiner Bildung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…This was evident in persulfate 96 and radiolysis-initiated emulsion polymerizations 92 . A dependence on initial monomer concentration has also been reported 97 .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…This was evident in persulfate 96 and radiolysis-initiated emulsion polymerizations 92 . A dependence on initial monomer concentration has also been reported 97 .…”
Section: Introductionmentioning
confidence: 83%
“…Dunn and Taylor 96 showed that, in the surfactant-free polymerization of an aqueous solution of VAc, a latex formed and its final particle number increased with persulfate concentration. Their explanation was the generally accepted notion that the charged end group derived from the initiator confers sufficient colloidal stability to form a stable latex.…”
Section: The Induced Decomposition Of Potassium Persulfatementioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers suggested that polymerization primarily occurs in the monomer-swollen polymer particles. [18][19][20][21] Thus, the graft polymerization of VAc was performed with water as a solvent.…”
Section: Grafting Of Vac Onto the Phb Film With Vac/water And Vac/metmentioning
confidence: 99%
“…This speed is in the range where the agitation has no noticeable e †ect on the rate of polymerization. 15 Samples of the reaction mixture were taken at various time intervals. These samples were very small so that the overall composition in the reaction vessel was not seriously a †ected.…”
Section: Polymerization Proceduresmentioning
confidence: 99%